(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Fungi are known as a major group of decomposers, possessing extensive physiological plasticity and high adaptive potential to various abiotic factors. Most cultivated species prefer acidic conditions for growth and development. While alkaliphilic and alkaline have been studied extensively, the study of fungi tolerant to high pH values is relatively recent. A number of Russian studies of micromycetes in soda lakes and salt marshes have made a significant contribution to this topic. The authors developed a comprehensive method for isolating and identifying the functional components of alkaline habitat communities, demonstrating for the first time the phenomenon of obligate alkaliphilia in fungi. This large-scale study raised new questions about the diversity, distribution, and role of alkaliphilic and alkalitolerant fungi in both consistently alkaline habitats (only a small fraction of which have been studied) and in habitats (saline and nonsaline) where alkalization can occur locally. The question of how alkali-tolerant fungi adapt to high pH values also remains relevant. Such data are fragmentary in the literature, with all studies conducted on alkalitolerants, not alkaliphiles. There is no information on the role of changes in the composition of soluble cytosolic carbohydrates and membrane lipids in adaptation to external pH, although these adaptation mechanisms are known to be among the most important under the influence of many other stress factors.